Belief in a Just World and Mental Toughness in Adolescent Athletes: The Mediating Mechanism of Meaning in Life - Tian, Siyu; Chen, Si; Cui, Yuming (Frontiers in Psychology, 2022)
Mental toughness is an essential component of adolescent athletes’ athletic careers and lives. Evidence supports the positive effect of belief in a just world on individual psychological development, but the relationship between belief in a just world and the mental toughness of adolescents has not been tested. In order to determine the influencing factors of mental toughness and explore effective strategies for improving adolescent athletes’ mental toughness, this study introduced the just world and life meaning theories to explore the relationship between belief in a just world, meaning in life (search for meaning/presence of meaning), and mental toughness. Based on the data of 1544 adolescent athletes from Yantai and Qingdao in Shandong Province, China, we tested a parallel mediation model that considered the search for meaning and the presence of meaning as mediators. The results were as predicted: there is a significant positive correlation between belief in a just world and mental toughness, while the relationship between belief in a just world and mental toughness was partially mediated by the search for meaning and the presence of meaning in life. Further, it is worth noting that the presence of meaning played a more influential role than the search for meaning. The results suggest that belief in a just world connects the mental toughness of adolescent athletes via meaning in life. Therefore, maintaining and promoting the level of belief in a just world and enhancing the sense of meaning in life may be an effective strategy to develop the mental toughness of adolescent athletes. The findings of this study can help to develop the mental toughness of adolescent athletes and help them maintain a high level of subjective and objective performance under the pressure of training and competition, providing practical guidance for coaches and administrators in the training of adolescent athletes.